Understanding communication research methods a theoretical and practical approach - Croucher, Stephen Michael 1978-; Cronn-Mills, Daniel (Routledge, 2015)
"Understanding Communication Research Methods helps students better grasp the theoretical and practical uses of method. While many texts describe methods only from a theoretical perspective, this book clearly illustrates practical applications and offers students an engaging how-to approach that draws from scholarship, real-life, and popular culture. The book defines all the main research traditions, illustrates key methods used in communication research, and provides level-appropriate applications of the methods through theoretical and practical examples and exercises.Each methods chapter includes a sample research paper written by an undergraduate student, accompanied by detailed explanations of the what, how, and why of the decisions that went into the research methods of the paper. These actual examples of student research provide a unique and approachable guide: students are given the opportunity to model their own work on their peers, while also reviewing the different decisions that might have influenced the direction and nature of the research.Comprehensive, innovative, and focused on the student, this book provides a valuable resource for instructors teaching an undergraduate course in research methods. Easy to follow and written directly for the undergraduate student, the book offers students practical reasons why they should care about research methods and a guide to actually conduct research themselves"--